2011
DOI: 10.1007/s00221-011-2700-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cortical plasticity, motor learning and BDNF genotype in healthy subjects

Abstract: There is good evidence that synaptic plasticity in human motor cortex is involved in behavioural motor learning; in addition, it is now possible to probe mechanisms of synaptic plasticity using a variety of transcranial brain-stimulation protocols. Interactions between these protocols suggest that they both utilise common mechanisms. The aim of the present experiments was to test how well responsiveness to brain-stimulation protocols and behavioural motor learning correlate with each other in a sample of 21 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 60 publications
6
82
3
1
Order By: Relevance
“…There are several possible explanations for the lack of relationship. There may be only partial overlap between the cortical processes moderated by brain stimulation and those involved in motor learning protocols (Li Voti et al, 2011). For example, performance of the rotor pursuit task used in this study also involves visual and subcortical striatal systems (Rajji et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for the lack of relationship. There may be only partial overlap between the cortical processes moderated by brain stimulation and those involved in motor learning protocols (Li Voti et al, 2011). For example, performance of the rotor pursuit task used in this study also involves visual and subcortical striatal systems (Rajji et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Di Lazzaro and colleagues have shown that while PAS and iTBS act primarily on cortical circuits generating late I-waves [3,4], cTBS acts primarily on cortical circuits generating I1 [5,6]. Li Voti and colleagues [17] examined the relationship between neuroplastic responses to different NBS protocols within a group of individuals and showed a positive relationship between the neuroplastic responses to 5 Hz repetitive TMS (rTMS) and iTBS. This suggests that 5Hz rTMS and iTBS engage common mechanisms important for short-term plasticity [17].…”
Section: Discussionmentioning
confidence: 99%
“…Li Voti and colleagues [17] examined the relationship between neuroplastic responses to different NBS protocols within a group of individuals and showed a positive relationship between the neuroplastic responses to 5 Hz repetitive TMS (rTMS) and iTBS. This suggests that 5Hz rTMS and iTBS engage common mechanisms important for short-term plasticity [17]. Relationships between multiple NBS protocols thought to be mediated by LTP-like mechanisms, however, were not examined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations